A case study for integrated sport sciences for an Olympic archer - Hung, T.-M.; Tang, W.-T.; Shiang, T. Y. (Journal of Medical and Biological Engineering, 2009)
Chinese Taipei organized and formed a sport science team for the National archery team targeting the 2004 Athens Olympic Games. Working with the National archery team for approximately one and a half years, Chinese Taipei archers achieved significant improvement in performance, winning a bronze medal in the women`s team event and 4th and 6th places in the women`s single events in the Athens 2004 Olympics. This report intends to provide an in-depth description on how sport science was applied to enhance archers` performance. Specifically, we report the intervention processes of psychological skill training (PST) and real-time technique analysis feedback for one female top archer who was the key member in securing the bronze medal in the women`s team event. As a case study, both qualitative and quantitative data were included. The procedures of the scientific support were sport science education for archers and coaches, diagnosis of archers, followed by designing an intervention program and determining the intervention and training effect before competition. Results indicated a positive feedback from the athletes and coaches achieving a significant improvement in performance. In addition to the exciting results, this model of sport science team integrated with athlete and coaches is also a promising approach to help elite athletes enhance sport performance. In conclusion, this case study is about integrating sport science in order to enhance archery performance. Because of the success of this model, its application for other competitive sports is promising and warrants for further investigation.